(untitled) (Review of Croatian History, 2021)
The aim of this paper is to provide an insight into how knowledge about dr. Franjo Tuđman was internationally created, namely the international context in which scientists and experts have produced factual truths about Croatia’s First President’s leadership, his role and accountability in the events that have marked the violent disintegration of former Yugoslavia, Croatia’s war of defense, and democratic transition. Developed discourse of the international scholarship about Yugoslav wars of disintegration and Croatia’s painful democratic transition is analyzed to determine how and in what way Dr. Franjo Tuđman is represented in selected publications available to the author of this paper. International scholarly production under the review is rather multidisciplinary with a variety of approaches, methodologies and theories providing rich data which in this case is studied juxtaposed to dominant transitional justice discourse framework. Such qualitative sociological research tries to deconstruct international scholarly context in which factual truths about dr. Franjo Tuđman were socially constructed by scholars and experts. Even though not always framed under the umbrella of transitional justice scholarship, developed discourse is Even though not always framed under the umbrella of transitional justice scholarship, developed discourse is nonetheless analyzed through critical lenses of social constructivism and approached in post-modernist sociological manner.